Beyond the Driverless Car: A Typology of Forms and Functions for Autonomous Mobility. Issue 1 (2nd January 2023) - Jones, Ryan; Sadowski, Jathan; Dowling, Robyn; Worrall, Stewart; Tomitsch, Martin; Nebot, Eduardo
ABSTRACT: The emergence of autonomous vehicles is attracting intense scrutiny for the transformative effects it may have on urban infrastructures and planning systems. Much of this scrutiny, though, has arguably focused on driverless passenger cars designed to operate on conventional carriageways. In this paper, we argue the car-centric vision of autonomous mobility limits our ability to identify and respond to the challenges posed by a suite of alternative vehicles found in hallways, footpaths, and (sub)urban precincts. We address this problem by presenting a typological description of autonomous vehicles beyond the driverless car. The paper describes their configuration and performance, identifies the spaces and use-cases they are associated with, and gestures to the challenges they raise for urban environments. The paper synthesises the observations generated through the typology into a set of complex questions demonstrated through the scenarioof a self-driving pod providing passenger transport at a university campus. It shows that, with a broad range of autonomous vehicles already operating in our cities, we need finer-grained analyses of how they are integrated into shared pedestrian spaces. The typology it offers provides a platform for this research by enhancing our comprehension of autonomous mobility forms, functions, and spaces. This will support further mobilities research on the proccesses and outcomes of urban experiments with autonomous systems.